2021
DOI: 10.4103/aer.aer_163_21
|View full text |Cite
|
Sign up to set email alerts
|

An Inquiry on Airway Management by McCoy Blade with Elevated Tip and Miller Straight Blade with Paraglossal Technique

Abstract: Background: Modifications of curved and straight laryngoscope blades have been used for airway management since a long time. While McCoy blade with an elevated tip is commonly used to intubate patients with anticipated difficult airway, the Miller's straight blade is used for intubations in children and less commonly adults. In this study, we revisit the paraglossal technique of Miller's straight blade as a method to improve laryngeal view especially in difficult intubations. Aim: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A study performed showed that it is necessary to constantly practice airway management methods including performing endotracheal intubation [41]. It is particularly important to learn how to use multiple laryngoscopes, as this can be useful in unconventional situations that require the modification of the technique, equipment, or body position [33].…”
Section: Discussionmentioning
confidence: 99%
“…A study performed showed that it is necessary to constantly practice airway management methods including performing endotracheal intubation [41]. It is particularly important to learn how to use multiple laryngoscopes, as this can be useful in unconventional situations that require the modification of the technique, equipment, or body position [33].…”
Section: Discussionmentioning
confidence: 99%